The Case for Revamping New Faculty Orientation: Integrating Case-Based Learning Into Faculty Onboarding - Mansoor Siddiqui; Dimitrios Papanagnou; Samantha Bruno; Karen Novielli (Association of American Medical Colleges, 2019)
Introduction New faculty orientation (NFO) for onboarding faculty members is replete with critical information and resources. Most NFO sessions are facilitated through lecture-based slide presentations. We employed a case-based learning (CBL) format to promote learner engagement through active use of the content being taught. We hypothesized that a CBL format would lead to improved learner satisfaction. Methods An inventory of topics presented at NFO was generated by reviewing previous orientation sessions. Cases and discussion questions were developed to link to specific content areas from previously delivered lectures. Participants were assigned cases with discussion questions, followed by a large-group debriefing. In 2014, 105 faculty members participated in NFO. An additional 232 faculty members participated from 2014 to 2017 with the revised format. Results Participants completed evaluations following each session. A specific item gauged the effectiveness of the format on a 9-point Likert scale. Scores were compared to 2014 evaluations using the unpaired Student t test. In 2014, participants rated the program format as 7.17 (mean) out of 9. Faculty orientation sessions in 2015, 2016, and 2017 scored 7.90 (p < .05), 8.00 (p < .05), and 8.40 (p < .01), respectively. Discussion We proposed a new format for NFO using a CBL-based format. Feedback highlighted faculty satisfaction with the new format. Qualitative feedback suggested that this new design in NFO sessions promotes learner engagement, networking, and collegiality. The format also models a pedagogy that faculty can implement directly in their respective teaching environments.